LAJU TUMBUH GULMA PADA BERBAGAI PUPUK ORGANIK DAN UKURAN BENIH DI PERTANAMAN KENTANG (Solanum tuberosum L.) DATARAN MEDIUM - Fina Anggraeni; Dadi Nurdiana; Jenal Mutakin (ZIRAA'AH MAJALAH ILMIAH PERTANIAN, 2024)
Weeds are one of the causes of the decline in potato production in the central plains. This research aimed to assess the diversity of weeds that appear on granola-variety potato plants (Solanum tuberosum L.) This research uses a quantitative approach by arranging frames measuring 50x50 cm in five locations spread diagonally. Weed samples were taken at 20 and 40 days after planting, and then the weed vegetation was analyzed using the index formula and weed dominance. The research found nine types of weeds, namely: Cyperus rotundus, Ageratum conyzoides L., Common purslane, Eleusine indica L. Gaertn, Commelia benghalensis, Panicum repens L., Amaranthus spinosus L., Gynura procumbens, and Bidens pilosa L. Analysis result the variety shows the level of weed diversity at 20 days after planting in the P0 treatment wich gives the best result with the lowest average value. Meanwhile, in weed diversity parameters at 60 days after planting, the highest average value was achieved by treatment P1, while the lowest average value was seen in treatment P3.